2018
DOI: 10.3389/fphys.2018.00713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Performance, Gross Efficiency and O2peak Characteristics on Subsequent Adaptations to Endurance Training in Competitive Cyclists

Abstract: The present study investigated the effects of initial levels of cycling performance, peak oxygen uptake (O2peak) and gross efficiency (GE) on the subsequent adaptations of these variables and their relationship following high-intensity training (HIT) designed to increase O2peak in competitive cyclists. Sixty cyclists (O2peak = 61 ± 6 mL kg-1 min-1) were assigned a 12-week training program consisting of twenty-four supervised high-intensity interval training sessions and ad libitum low intensity training. GE wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…This combination is in contrast to previous studies showing slightly reduced work economy or gross efficiency when boosting VO 2max over a short period, like e.g. Skovereng et al 26 and Vandbakk et al 25 . Skovereng et al found a moderate correlation between improved VO 2max and deteriorated gross efficiency in cycling, which may indicate a deteriorated work economy although care should be taken when comparing oxygen cost results vs. gross efficiency results.…”
Section: Dp-vo 2peak and %Run-vo 2maxcontrasting
confidence: 99%
See 1 more Smart Citation
“…This combination is in contrast to previous studies showing slightly reduced work economy or gross efficiency when boosting VO 2max over a short period, like e.g. Skovereng et al 26 and Vandbakk et al 25 . Skovereng et al found a moderate correlation between improved VO 2max and deteriorated gross efficiency in cycling, which may indicate a deteriorated work economy although care should be taken when comparing oxygen cost results vs. gross efficiency results.…”
Section: Dp-vo 2peak and %Run-vo 2maxcontrasting
confidence: 99%
“…a much shorter interval duration and a much higher intensity than in the present study. On the other hand, the mean intensity for 4 • 4 minutes protocol in Skovereng et al 26 was 89% HR max . This is in line with the durations and intensities of the present study, which was 90-95% of HR peak in DP, and thus approximately 88-93% of HR max .…”
Section: Dp-vo 2peak and %Run-vo 2maxmentioning
confidence: 87%
“…We and others have previously shown that efficiency can change and that acute decreases in efficiency can allow a higher power output under certain conditions (5,7). This trade-off could also explain why there are no differences in efficiency between competitive cyclists and noncyclists (5) and the seemingly controversial findings that efficiency has been found to both increase (3) and decrease (8) after training.…”
mentioning
confidence: 83%
“…As these results show, the initial level of performance significantly conditions the adaptations generated by training. Recent research (Skovereng et al, 2018) has also shown that there are statistically significant differences between the initial level of performance and VO2peak and subsequent adaptations following a 12-week high intensity interval training program in trained cyclists. Yet, these authors note that the small and moderate effects indicate a limited influence on training practice.…”
Section: Discussionmentioning
confidence: 99%